Groundwater resources development for a sustainable water supply in developing countries: A case study of Ghana - Victor Ofori Agyemang (Cleaner Water, 2025)
The hydrogeology of Ghana has been classified into five main hydrogeological provinces. Generally, the hydrogeology of the country is mainly controlled by secondary hydraulic properties caused by weathering and fracturing. About 2.9 %, 21.6 %, 45.6 %, 27.1 %, and 2.8 % of the landmass of Ghana have very good, good, moderate, bad, and very poor groundwater potential respectively. Variable levels of groundwater mineralization in geological units are seen in the overall geochemistry of the country. The primary issues with groundwater quality in the country are high concentrations of fluoride, arsenic, manganese, iron, hardness, and salinity in some localities. Poor selection and application of geophysical methods, shallow drilling depths above productive fractured zones, complete reliance on thin shallow aquifers, poor construction of drilled boreholes, lack of maintenance of mechanized boreholes, and limited aquifer recharge in some parts of the country are some of the potential causes of frequent borehole drilling failure, low borehole yields, and drying up of hand-dug wells and some boreholes during the dry seasons. For effective and efficient groundwater development, it is recommended that groundwater exploration be conducted to a minimum depth of 200 m using the combined application of the electromagnetic method, or two-dimensional magnetotelluric, two-dimensional electrical resistivity, and two-dimensional induced polarization methods in the order presented. Again, both technological such as managed aquifer recharge and policy measures should be implemented to balance groundwater usage with aquifer replenishment to ensure sustainable management of the resources.